Was Jesus Right to Eat with Sinners and Tax Collectors? - Kilgallen, John J. (Biblica, 2012)
All Jewish religious teachers wanted sinners to repent; how one achieves this was disputed, as was Jesus’ choosing to associate with sinners in their houses and at their meals. Four times Luke describes Jesus as fraternizing with sinners, which violated Jewish pious practice. The first three times (chaps. 5, 7 and 15) Jesus underlines his motive for this conduct and its value; the fourth time (chap. 19), and rather late in the Gospel, Luke shows that indeed Jesus’ method proved true, i.e. the wisdom of his conduct was shown justified by repentant children of God.